2014
DOI: 10.7860/jcdr/2014/10849.5327
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric Lymph Node Hamartoma (Castleman’s Disease) in Association with Superior Mesenteric Arteriovenous Fistula

Abstract: We present a case of 21-year-old female patient with history of pain abdomen and abdominal distension. The patient also had oedema of the limbs, puffiness of the face, pallor and palpable mass in the abdomen. Ultrasonography of the abdomen and computed tomographic angiogram was done and it showed presence of vascular mass along with arteriovenous malformation in the mesentry of small gut between distal branches of superior mesenteric artery and vein. Surgical excision of the mass with ligation and division of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…On reviewing the literature we found that Vikasdeep Goyal et al, described similar case lymphoid hyperplasia situated in the mesenteric lymphnode associated with AV fistula and anaemia whereas in our case the cervical group of lymhnode was involved with few pressure symptoms and without anaemia [8]. Only few cases of cervical Castleman's disease have been reported in the literature and most of them presented as a solitary neck mass [9].…”
Section: Case Reportsupporting
confidence: 45%
“…On reviewing the literature we found that Vikasdeep Goyal et al, described similar case lymphoid hyperplasia situated in the mesenteric lymphnode associated with AV fistula and anaemia whereas in our case the cervical group of lymhnode was involved with few pressure symptoms and without anaemia [8]. Only few cases of cervical Castleman's disease have been reported in the literature and most of them presented as a solitary neck mass [9].…”
Section: Case Reportsupporting
confidence: 45%